Literature Review on Antecedents of Customer Switching Behavior - Darmawan, Didit (Metromedia, 2022)
Customer switching behavior occurs when customers switch away from the initial product they used and choose another product. This phenomenon is interesting to study along with the intense competition and technological developments that have led to many alternative products and services for consumers to choose from. This study aims to analyse the development of research in the field of service switching behavior carried out by customers in banks. The method used is literature review, namely by analysing scientific articles published from 2010 to 2021. The results of the review study on several scientific articles found that the causes of customer switching behavior are service quality, trust, satisfaction, loyalty, price, bank reputation, bank image, advertising, demographics, location, interest rates, switching costs, attractiveness, ease of use, subjective norms, beliefs and attitudes, customer value, purchase intention, service strategy to switch